2018
DOI: 10.1007/s13204-018-0703-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring dynamic electrochemical processes with in situ ptychography

Abstract: The present work reports novel soft X-ray Fresnel CDI ptychography results, demonstrating the potential of this method for dynamic in situ studies. Specifically, in situ ptychography experiments explored the electrochemical fabrication of Codoped Mn-oxide/polypyrrole nanocomposites for sustainable and cost-effective fuel-cell air-electrodes. Oxygen-reduction catalysts based on Mn-oxides exhibit relatively high activity, but poor durability: doping with Co has been shown to improve both reduction rate and stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Ptychography is one of the most advanced X-ray microscopy techniques for high-resolution imaging, because it uses a focused beam in conjunction with its scanning over the sample making it suitable for large samples (with sizes ranging from some micrometers to millimeters) and it is compatible with other scanning microscopy and electrochemical systems. [63][64][65] This technique stands out not only for achieving a spatial resolution beyond the size of the focused beam.…”
Section: Ptychography and Bcdimentioning
confidence: 99%
“…Ptychography is one of the most advanced X-ray microscopy techniques for high-resolution imaging, because it uses a focused beam in conjunction with its scanning over the sample making it suitable for large samples (with sizes ranging from some micrometers to millimeters) and it is compatible with other scanning microscopy and electrochemical systems. [63][64][65] This technique stands out not only for achieving a spatial resolution beyond the size of the focused beam.…”
Section: Ptychography and Bcdimentioning
confidence: 99%
“…Only a few applications of in situ and operando spectroptychography have emerged to date. 39 In situ spectroptychography was examined at the Co L 3 edge (16 energies) for a working electrode of a Mn–Co/polypyrrole nanocomposite that had been subjected to 100 electrodeposition cycles. In these examples, the sample is stable over the time scale of the spectroscopic scans.…”
Section: Other Aspects Of Spectroptychographymentioning
confidence: 99%
“…Indeed, the redundant information due to the oversampling allows computer algorithms to reconstruct reliably both the sample transmission function and the illuminating probe, recovering the amplitude and phase of both these signals. As in classical SXTM, by reconstructing a stack of images acquired at photon energies across the absorption edge of a specific chemical element, ptychography allows for XANES-type studies, as demonstrated in [64,65], providing sub-micrometric resolution chemical speciation.…”
Section: Ptychography and Coherent Diffraction Imaging (Cdi)mentioning
confidence: 99%
“…In addition to ptychography experiments, the beamline has successfully tested the keyhole-CDI technique [61], which, by being a single-shot technique, is, in general, preferable for in situ dynamic studies, such as monitoring the dynamics of electrodeposition [64,65], but which can also be used for biological samples [66].…”
Section: Ptychography and Coherent Diffraction Imaging (Cdi)mentioning
confidence: 99%